Narratives on the curricularization of cross cultural management and contributions to the internationalization of higher education - de Almeida Bizarria, Fabiana Pinto; Moreira, Márcia Zabdiele; Barbosa, Flávia Lorenne Sampaio; Córdova, Irma Eufemia Abrigo; Santos, Gabriel Castro (Frontiers in Education, 2024)
IntroductionThe objective of the research was to argue about the urgency of the Curricularization of Cross-Cultural Management, to provide better preparation for students in the face of social, economic and political dynamics.MethodsThe research takes a qualitative approach and uses a revisional methodology, considering articles published on the Web of Science and Scopus, with a search conducted in July 2024, with the descriptor “Cross-Cultural Management” considering the period from 2012 to 2024.ResultsThe narrative literature review was used, while the reading and choice of texts for the research corpus considered attention to the CCM approach, contributing to the construction of the argument about the curricularization of cross-cultural management.DiscussionIt is concluded that research and teaching on contemporary cross cultural management need to reflect on the varied worldviews and different paradigms, with attention to (i) digital transformation and virtual education; (ii) learning, connectivism, and formative experience; (iii) knowledge management and communities of practice; and (iv) conflict management.